Penerapan Pembelajaran Tahfidz Al-Qur'an Dan Implikasinya Dengan Adab Menuntut Ilmu Peserta Didik - Nyarminingsih, Nyarminingsih; Ruwandi, Ruwandi (Kutubkhanah, 2023)
Abstract: The tahfidz program in the current era is widely implemented in every school, on the other hand, tragedies often occur and students lack manners towards teachers. So the aim of this research is to analyze the design of tahfidz learning, the supporters and obstacles to the implementation of tahfidz learning, the implications of tahfidz learning for cultivating the etiquette of studying in students of superior programs at MTs N Salatiga. Research Method This research uses a naturalistic qualitative approach. Data collection techniques use observation, interviews, documentation methods. The data sources in this research are divided into two, namely: primary data sources and secondary data sources. Meanwhile, the data analysis process includes data reduction, data presentation and drawing conclusions. The results of the research are (1) The implementation of Tahfidz Al Qur'an learning is divided into three stages. First, planning, namely: acceptance selection stage, memorizing targets and memorizing methods. Second, the implementation, namely: the opening begins with the dhuha prayer, praying, and providing motivation, Teacher Tahfidz guides students in memorizing. The closing activities are: murojaah together and closing prayer. Third, the evaluation stage consists of daily evaluations, fortnightly evaluations, mid-semester or end-of-semester evaluations, simul Qur'an evaluations. (2) Supporting and inhibiting factors. Supporting factors include motivation, competent teachers, student intelligence, parents, and school infrastructure. Meanwhile, inhibiting factors include the lack of tahfidz learning hours, feeling lazy and not consistent in memorizing, and the external environment. (3) The implications of learning Tahfidz Al Qur'an in cultivating the etiquette of seeking knowledge at MTs N Salatiga, namely sincere intentions, respecting teachers and appreciating knowledge, Istiqomah and consistently murojaah memorizing the Al Qur'an.